Dirtying Linen: Re‐evaluating the sustainability of domestic laundry. (March 2016) - Yates, Luke; Evans, David
Abstract: In tackling and negotiating responsibility for anthropogenic climate change, governments and businesses are increasingly concerned with shaping 'consumer behaviour', understood broadly as the ways in which people acquire, appropriate and appreciate goods and services. One intervention considered successful in this respect has been that of encouraging the low‐temperature washing of laundry in the UK in the last decade. This paper draws on data from a quantitative survey of laundry practices conducted in Britain in 2013 ( N = 1502) in order to situate the intervention, and the phenomenon of low‐temperature washing, in its wider socio‐cultural context. Our starting point is that laundry habits are a useful example of a household practice in which changes in consumer behaviour have occurred, yet which continue to be increasingly environmentally problematic. Our analysis examines the use of washing machines and the temperature at which people do their laundry in detail; however, it also explores the broader processes through which clothing and other items become designated 'dirty' and go on to become 'clean'. We argue that, in contrast to the well‐documented hegemonic position of the washing machine in UK homes, there is much diversity in how households organize the other tasks involved in doing laundry, particularly in separating, sorting and drying, with important implications for energy use. To conclude, we reconsider low‐temperature washing as an intervention, and outline some policy implications of a more thorough understanding of how laundry, and domestic consumption more generally, is currently handled in the UK. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment